[Gas pains ; Dancers ; Straight from the heart [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Tackles the full supply and the government's energy conservation measures ; discusses the plight of stripteasers ; and an interviews with Jose Mari Chan as a music composer.